2016
DOI: 10.1016/j.biopsych.2015.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Vagus Nerve Stimulation Modulates Default Mode Network in Major Depressive Disorder

Abstract: Background Depression is the most common form of mental disorder in community and health care settings and current treatments are far from satisfactory. Vagus nerve stimulation (VNS) is an FDA-approved somatic treatment for treatment-resistant depression. However, the involvement of surgery has limited VNS only to patients who have failed to respond to multiple treatment options. Transcutaneous VNS (tVNS) is a relatively new, non-invasive VNS method based on the rationale that there is afferent / efferent vagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
255
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 293 publications
(280 citation statements)
references
References 75 publications
20
255
1
4
Order By: Relevance
“…Some patients (n = 49) were also invited to participate in an fMRI study at baseline and after 4 weeks of treatment to investigate the brain resting state functional connectivity changes before and after one month of taVNS as compared to sham taVNS. Please see the original publication for more details (Fang et al, 2015). The present study will focus on the clinical outcomes of a 12-week treatment of the multiple-center clinical trial, which was not reported in the previous brain imaging study.…”
Section: Methodsmentioning
confidence: 99%
“…Some patients (n = 49) were also invited to participate in an fMRI study at baseline and after 4 weeks of treatment to investigate the brain resting state functional connectivity changes before and after one month of taVNS as compared to sham taVNS. Please see the original publication for more details (Fang et al, 2015). The present study will focus on the clinical outcomes of a 12-week treatment of the multiple-center clinical trial, which was not reported in the previous brain imaging study.…”
Section: Methodsmentioning
confidence: 99%
“…In order to overcome the disadvantages of classic VNS, we developed taVNS. And we accidently found that taVNS could improve patients sleeping conditions in depressed patients [29] and in epilepsy patients [30] during our clinical studies process. In addition, taVNS can trigger melatonin secretion, which may be one of the key mechanisms of improving sleeping conditions in patients [31].…”
Section: Resultsmentioning
confidence: 97%
“…Auricular acupuncture (AA), which is often recommended as treatment for insomnia [20], inspired us to invent transcutaneous auricular vagus nerve stimulation (taVNS) years ago (Figure 4). We accidently found that taVNS could improve patients sleeping conditions in depressed patients [29] and in epilepsy patients [30] during our clinical studies process. We considered that taVNS is a promising alternative therapy for insomnia disorder with a bright future.…”
Section: Resultsmentioning
confidence: 97%
“…Evidence for the role of a nervous component in neuropsychiatry was shown by the use of vagus nerve stimulation (VNS) for treatment-resistant mood disorders such as depression (Albert et al, 2015). VNS is an FDA approved treatment that improves depressive symptoms (Albert et al, 2015;Fang et al, 2015;Shiozawa et al, 2014). Hypofunction of the parasympathetic vagus nerve was also shown to be involved in the pathophysiology of schizophrenia (Bar et al, 2008(Bar et al, , 2005(Bar et al, , 2012Malaspina et al, 1997;Boettger et al, 2006;Ostermann et al, 2013).…”
Section: Different Pathways Involved In the Neuroinflammatory Pathogementioning
confidence: 96%